2016
DOI: 10.1007/s00068-016-0719-9
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative inflammatory response in major fracture: do geriatric patients behave differently?

Abstract: Both the operative treatment of fractures in a middle-aged (SP) and a geriatric group (PF) lead to significant increasing of IL-6 levels. In view of a comparative surgical burden, these data suggest that age may be a confounding factor for a surgery induced pro-inflammatory response in the early postoperative stage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Similarly, a trend towards an age-dependent increase for IL-6 plasma cytokine levels was observed in aged rodents that underwent minor surgery. Consistent with these findings, a clinical study demonstrated that aged patients that received surgical treatment have higher IL-6 serum levels with respect to middle-aged surgical patients (Thaeter et al, 2016). This may be explained, at least in part, by the amplified production of proinflammatory cytokines by aged peripheral blood mononuclear cells (PBMCs) (Fagiolo et al, 1993).…”
Section: Circulating Inflammatory Markers In Serum Plasma and Csfmentioning
confidence: 67%
“…Similarly, a trend towards an age-dependent increase for IL-6 plasma cytokine levels was observed in aged rodents that underwent minor surgery. Consistent with these findings, a clinical study demonstrated that aged patients that received surgical treatment have higher IL-6 serum levels with respect to middle-aged surgical patients (Thaeter et al, 2016). This may be explained, at least in part, by the amplified production of proinflammatory cytokines by aged peripheral blood mononuclear cells (PBMCs) (Fagiolo et al, 1993).…”
Section: Circulating Inflammatory Markers In Serum Plasma and Csfmentioning
confidence: 67%
“…Screening of full-text articles identified a total of 45 studies that met eligibility criteria. 17–61 Search results and study selection are summarized in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…For example, proximal femur fracture increased serum concentrations of IL-6 more in patients older than 70 years than in patients younger than 50 years [119]. Furthermore, after surgery, IL-6 concentrations increase more rapidly and remain elevated longer in elderly than middle aged people [120,121]. Based on these observations, Hazeldine et al proposed a model of age-differences in the inflammatory response to injury (Figure 6) [121].…”
Section: Introductionmentioning
confidence: 99%